Design of an Optimal Automation System: Finding a Balance between a Human’s Task Engagement and Exhaustion - Klein, Michel; van Lambalgen, Rianne (Modern Approaches in Applied Intelligence, 2011)
In demanding tasks, human performance can seriously degrade as a consequence of increased workload and limited resources. In such tasks it is very important to maintain an optimal performance quality, therefore automation assistance is required. On the other hand, automation can also impose additional demands on a person monitoring the system and it will likely reduce the person’s awareness of the situation. Therefore, automation should be adapted to the human’s state in order to keep the human in the loop. In this paper an agent model is proposed that calculates a person’s workload and engagement to an automated task. Based on this agent model, an intelligent support system can provide different types of automation and aims at adapting to the human state such that an optimal balance is found between exhaustion and task engagement.